Features of cytomegalovirus infection and evaluation of cytomegalovirus-specific T cells therapy in children’s patients following allogeneic hematopoietic stem cell transplantation: A retrospective single-center study - Ruan, Yongsheng; Luo, Tingting; Liu, Qiujun; Liu, Xuan; Chen, Libai; Wen, Jianyun; Xiao, Yuhua; Xie, Danfeng; He, Yuelin; Wu, Xuedong; Feng, Xiaoqin (Frontiers in Cellular and Infection Microbiology, 2022)
Cytomegalovirus (CMV) infection remains a critical cause of mortality after allogeneic hematopoietic stem cell transplantation (allo-HSCT), despite improvement by pre-emptive antivirus treatment. CMV-specific cytotoxic T lymphocytes (CMV-CTL) are universally used and proven well-tolerance after allo-HSCT in adult clinical trials. However, it is not comprehensively evaluated in children’s patients. Herein, we conducted a retrospective study to determine the risk factors of CMV infection and evaluation of CMV-CTL in children patients who underwent allo-HSCT. As result, a significantly poor 5-year overall survival was found in the CMV infection group (87.3 vs. 94.6%, p=0.01). Haploidentical HSCT (haplo-HSCT) was identified as an independent risk factor for CMV infection through both univariate and multivariate analyses (p<0.001, p=0.027, respectively). Furthermore, the cumulative incidence of CMV infection was statistically higher in the haplo-HSCT group compared to the HLA-matched donor group (44.2% vs. 21.6%, p<0.001). Finally, the overall response rate of CMV-CTL was 89.7% (26/29 patients) in CMV infection after allo-HSCT. We concluded that CMV infection following allo-HSCT correlated with increased mortality in children’s patients, and haplo-HSCT was an independent risk factor for CMV infection. Adoptive CMV-CTL cell therapy was safe and effective in pediatric patients with CMV infection.